تحليل قياسي للإنتاج السمكي في مصر - بهلول، أسماء محمد الطوخي; البطح، فاطمة أحمد مصطفي (جامعة المنصورة - كلية الزراعة, 2018)
The study examined the factors affecting production, consumption and fish imports in order to narrow the gap between production and consumption so as not to negatively affect the development rates in Egypt and alleviate the deficit of the Egyptian trade balance. The average consumption was 16.8 million tons, while production was estimated at 15.1 million tons. Million tons during the period (2012-2016).The problem of research is that Egypt faces a population increase of about 2.6 million people per year and despite the increase in fish production, the corresponding increase in consumption is increasing at a higher rate, leading to an increase in Egyptian imports, which is a burden on the Egyptian agricultural trade balance. While it is clear that the research aims to analyze the structure of Egyptian foreign trade for fish by determining the most important economic factors affecting both production and consumption and imports of fish. By building a standard model for the analysis of the foreign fish market. The research was based on descriptive and quantitative analysis using various measures such as relative importance and averages. Simple regression analysis was used. Simultaneous Equation Systam was also used in the design of a standard model for analyzing the structure of Egyptian imports of fish. Using the equation of consumption and the most important factors and the equation of production and the equation of imports and factors and then a tariff equation and the study found that the best way to estimate in this case is the method of squares of the two phases (2SLS) Two Stages Least Squares Method where this method gives more efficient estimates, Mainly based on statistical data published and unpublished by several bodies such as the Ministry of Agriculture, the Central Agency for Public Mobilization and Statistics and the General Authority for Fisheries Development. The results showed that the most important factors affecting the quantity consumed fish population and the relationship is positive while there is an inverse relationship between the quantity consumed and the real domestic price and import price. While the most important factors affecting the local production of fish were the direct consumption of fish and the export price, while the opposite relationship of both the import price and the number of fishermen. As for fish imports, the inverse relationship between the quantity of fish imports, both the quantity consumed and the import price, and the existence of a positive correlation between imports and real national income were shown. The study concluded that while the factors affecting the Egyptian imports of fish remain the same, the probability of the increase in the Egyptian import bill increases year after year, and the consequent increase in the deficit in the Egyptian trade balance, as well as in the agricultural trade balance. Increasing the self-sufficiency of fish through new fish farming projects such as the Barka Ghalioun project in Kafr El-Sheikh. This fish farming project will produce 25,000 tons. This will reduce the fish gap resulting from the population increase and thus increase the consumption of fish.
بدراسة العوامل المؤثرة على الإنتاج والاستهلاك والواردات السمكية وذلك لتضييق الفجوة بين الإنتاج والاستهلاك حتى لا يؤثر سلبا على معدلات التنمية في مصر، وتخفيف عجز الميزان التجاري المصري، هذا وقد بلغ متوسط الاستهلاك 16.8 مليون طن في حين قدر الإنتاج بنحو 15.1 مليون طن وتقدر الفجوة السمكية بحوالي 20.6 مليون طن، وذلك خلال الفترة (2012-2016). وتتمثل مشكلة البحث في أنه تواجه مصر زيادة سكانية تصل لحوالي 2.6 مليون نسمة سنويا وعلى الرغم من زيادة الإنتاج من الأسماك إلا أن الزيادة المقابلة في الاستهلاك تزيد بمعدل أكبر مما يؤدي إلى زيادة الواردات المصرية والتي تمثل عبء على الميزان التجاري الزراعي المصري في حين يتضح أن البحث يستهدف تحليل هيكل التجارة الخارجية المصرية للأسماك من خلال تحديد أهم العوامل الاقتصادية المؤثرة عى كل من الإنتاج والاستهلاك والواردات للأسماك. وذلك عن طريق بناء نموذج قياسي لتحليل سوق التجارة الخارجية للأسماك. واعتمد البحث على أسلوب التحليل الوصفي والكمي باستخدام بعض المقاييس المختلفة مثل الأهمية النسبية والمتوسطات، واستخدم تحليل الانحدار البسيط، كما تم استخدام المعادلات الآتية Equation Systam Simultaneous في تصميم نموذج قياسي لتحليل هيكل الواردات المصرية من الأسماك. وذلك باستخدام معادلة الاستهلاك وأهم العوامل المؤثرة ومعادلة الإنتاج ومعادلة الواردات والعوامل المؤثرة ثم معادلة تعريفية وتوصلت الدراسة إلى أن أفضل الطرق للتقدير في هذه الحالة هي طريقة المربعات الصغرى ذات المرحلتين Two Stages Least Squares Method (2SLS) حيث تعطي هذه الطريقة تقديرات أكثر كفاءة، واعتمد البحث بصورة أساسية على البيانات الإحصائية المنشورة وغير المنشورة من عدة جهات مثل وزارة الزراعة والجهاز المركزي للتعبئة العامة والإحصاء والهيئة العامة لتنمية الثروة السمكية. وتبين من نتائج الصورة المختزلة أن أهم العوامل المؤثرة على الكمية المستهلكة من الأسماك عدد السكان والعلاقة طردية في حين وجود علاقة عكسية بين الكمية المستهلكة والسعر المحلي الحقيقي وسعر الاستيراد. في حين تبين أن أهم العوامل المؤثرة على الإنتاج المحلي من الأسماك طرديا هي الاستهلاك المحلي من الأسماك والسعر التصديري بينما اتضح العلاقة العكسية لكلا من سعر الاستيراد وعدد الصيادين. أما عن الواردات من الأسماك فقد اتضح العلاقة العكسية بين كمية الواردات السمكية وكلا من الكمية المستهلكة وسعر الاستيراد ووجود علاقة طردية للواردات مع الدخل القومي الحقيقي. وتوصل البحث إلى أنه مع بقاء العوامل المؤثرة على الواردات المصرية من الأسماك كما هي فإن احتمالات ارتفاع فاتورة الواردات المصرية تتزايد عام بعد آخر، وما يترتب على ذلك من تزايد العجز في الميزان التجاري المصري، وكذلك في الميزان التجاري الزراعي، الأمر الذي يتطلب ضرورة العمل على رفع نسبة الاكتفاء الذاتي من الأسماك من خلال المشروعات الجديدة من الاستزراع السمكي مثل مشروع بركة غليون بكفر الشيخ فهذا المشروع للاستزراع السمكي سينتج 25 ألف طن" وهذا سوف يقلل من الفجوة السمكية الناتجة عن الزيادة السكانية وبالتالي زيادة الاستهلاك من الأسماك.
Keywords: الإنتاج السمكي -- مصر -- الزيادة السكانية -- الإستهلاك السمكي